Caribbean small island developing states must incorporate water quality and quantity in adaptive management of the water-energy-food nexus - Crisman, Thomas L.; Winters, Zachary S. (Frontiers in Environmental Science, 2023)
The 10 Small Island Developing States (SIDS) of the Caribbean in this study have unsustainable water-energy-food Nexus conditions, with stress becoming more acute via climate change, population demographics and increasing tourist demands. Water resources are limited, and wastewater treatment is inadequate or missing. Nature-based solutions (NBS), especially constructed wetlands, are effective treatment options for all SIDS and have added value for recreation, conservation and product development. On islands with abundant rainfall, NBS treated water adds little to total water resources, but can be important for small scale agriculture. Rainwater harvesting is an important alternative water source for individual households and small communities, but water reuse from tourist infrastructure has the greatest potential for SIDS to reach water sustainability, while protecting coastal waters from sewage pollution. Tourism is a two-edged sword. It swells populations and associated water demand significantly and can degrade coastal waters if wastes are not treated effectively. However, a partnership among the tourist industry, local communities and national government must be given top priority to ensure sustainability of the Water-Energy-Food (WEF) Nexus in the face of progressively increasing tourist numbers and pressures. Effective governance is needed at the island and regional level to develop sound adaptative management approaches for sustainability.